2016
DOI: 10.1371/journal.ppat.1005359
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Bacterial D-Serine Uptake System Links Host Metabolism and Virulence

Abstract: The ability of any organism to sense and respond to challenges presented in the environment is critically important for promoting or restricting colonization of specific sites. Recent work has demonstrated that the host metabolite D-serine has the ability to markedly influence the outcome of infection by repressing the type III secretion system of enterohaemorrhagic Escherichia coli (EHEC) in a concentration-dependent manner. However, exactly how EHEC monitors environmental D-serine is not understood. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 76 publications
1
67
0
Order By: Relevance
“…Alternative names exist for cyuP (cdsA and dlsT), cyuA (cdsB), and cyuR (cutR and decR) (21)(22)(23). Nonetheless, we propose the cyu designation because the cds designation (for CDP-diglyceride synthetase) and the cut designation (for copper utilization) are already in use, and the dec designation (for detoxification of cysteine) does not suggest expression of these genes and the phenotype of mutants lacking these genes when cysteine is not toxic (described below).…”
mentioning
confidence: 99%
“…Alternative names exist for cyuP (cdsA and dlsT), cyuA (cdsB), and cyuR (cutR and decR) (21)(22)(23). Nonetheless, we propose the cyu designation because the cds designation (for CDP-diglyceride synthetase) and the cut designation (for copper utilization) are already in use, and the dec designation (for detoxification of cysteine) does not suggest expression of these genes and the phenotype of mutants lacking these genes when cysteine is not toxic (described below).…”
mentioning
confidence: 99%
“…However, we have observed growth tolerance of EHEC irrespective of sulA upregulation, suggesting that there are downstream factors that counteract the effects of increased SulA expression. What is most intriguing is that this tolerance appears to be unique to EHEC, given that a UPEC ⌬dsdA mutant is unable to tolerate D-serine accumulation and shows arrested growth under the same conditions (41). These results suggest EHEC-specific regulation that counteracts recA induction by D-serine.…”
Section: Discussionmentioning
confidence: 97%
“…In this work, we found that D-serine accumulation could actually enhance the mutation rate of the population through RecA production and that this was dependent on D-serine accumulation in the cell. Interestingly, D-serine accumulation in a UPEC ⌬dsdA background is a much less tolerated event and exemplifies a fitness defect under these conditions (41). In the UPEC ⌬dsdA mutant, D-serine accumulation also results in a higher recA induction than that of EHEC, suggesting that this stress may account for the apparent adaptation to D-serine tolerance in EHEC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations